Women’s Agency in the Dune Universe - Kennedy, Kara. author. aut Link
XIII, 239 p.
Keywords: This book undertakes the first large-scale analysis of women’s agency in Frank Herbert’s six-book science fiction Dune series. Kara Kennedy explores how female characters in the Bene Gesserit Sisterhood—from Jessica to Darwi Odrade—secure control and influence through five avenues of embodied agency: mind-body synergy, reproduction and motherhood, voices, education and memory, and sexuality. She also discusses constraints on their agency, tensions between individual and collective action, and comparisons with other characters including the Mentats, Bene Tleilaxu, and Honored Matres. The book engages with second-wave feminist theories and historical issues to highlight how the series anticipated and paralleled developments in the women’s liberation movement. In this context, it addresses issues regarding sexual difference and solidarity, as well as women’s demand to have control over their bodies. Kennedy concludes that the series should be acknowledged as a significantcontribution to the genre as part of both New Wave and feminist science fiction. Kara Kennedy is a researcher, writer, and educator in the areas of science fiction, digital literacy, and writing. She is an avid scholar of Dune who has lectured and published on various topics including world-building. She posts literary analyses of Dune for a mainstream audience on her blog DuneScholar.com.